The solution of the system of equations is (-1 , -1)
Step-by-step explanation:
To solve the system of linear equations by substitution method
∵ x + y = -2 ⇒ (1)
∵ y = 4x + 3 ⇒ (2)
- Substitute y in equation (1) by equation (2)
∴ x + (4x + 3) = -2
- Add like terms
∴ (x + 4x) + 3 = -2
∴ 5x + 3 = -2
- Subtract 3 from both sides
∴ 5x = -5
- Divide both sides by 5
∴ x = -1
- Substitute the value of x by -1 in equation (20 to find y
∴ y = 4(-1) + 3
∴ y = -4 + 3
∴ y = -1
The solution of the system of equations is (-1 , -1)
Learn more:
You can learn more about system of linear equations in brainly.com/question/6075514
#LearnwithBrainly